Proviviparus talbragarensis gen. et sp. nov., the first viviparid snail from the Late Jurassic of Australia. Issue 3 (3rd July 2021) - Frese, Michael; Ponder, Winston
Abstract: Extinct freshwater snails of the family Viviparidae can be found on all continents with the exception of Madagascar and Antarctica. These snails are usually thought to have evolved in the Early Jurassic of Laurasia. Our findings suggest that viviparids may have achieved an almost worldwide distribution by the Late Jurassic. Here we report viviparid snails from the Upper Jurassic Talbragar Fish Bed in New South Wales, Australia, and describe them as a new genus and species. This represents the first reliable record of the family Viviparidae from the Jurassic of Gondwana. One specimen shows a thin operculum and in another there is evidence of brooding. Michael Frese [ michael.frese@canberra.edu.au ], Faculty of Science and Technology, University of Canberra, Canberra, Australian Capital Territory 2601, Australia and Australian Museum Research Institute, College Street, Sydney, New South Wales 2010, Australia; Winston Ponder [wponder@bigpond.net.au ], Australian Museum Research Institute, College Street, Sydney, New South Wales 2010, Australia .